Assessment of strain and deformation of the «bone – fixateur» system in osteosynthesis of the lateral malleolar fractures - Golovakha, Maksim; Kozhemyaka, Maksym; Panchenko, Sergey; Krasovskiy, Vasil (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Injuries of the ankle joint is one of the main causes of disability and poor outcomes which are caused by inadequate reposition, imperfect osteosynthesis and secondary displacement of fragments. Qualitative and reliable stabilization of the lateral malleolar bone fragments essentially depends on the design of the fixateur. Objective: based on the analysis of the stress-strain state of the system «bone – fixateur» to evaluate the effectiveness of the proposed fixateur for osteosynthesis of infrasyndesmotic lateral malleolar fractures. Methods: The finite element analysis with ANSYS software complex and model of the system «bone – fixateur» that limited by the fibula the shape of which was simplified for the construction being symmetric in the frontal plane. Models were built in the program AUTOCAD. Geometry of sections of bone meets the real size of the adult. The criterion for evaluation of the efficiency of plate-fixateur selected values of stresses in bone tissue and movement of the fragment points — opening of the fracture. An additional criterion was the value of stresses in the plate. Results revealed that the greatest amounts in bone tissue are normal stresses σ acting in the direction of the fibular axis. They occur in cortical bone at the edges of the holes for the screws. Stressed state of bone turned significantly heterogeneous. For heavy loads (half from critical for syndesmotic ligaments breakage) stresses in the plate are dangerous. However, they occur in the areas of concentration but the actual loads will be lower. The most significant deviations of the stress state of the bone occur at the edges of the holes for the screws, in the joints cortical and spongiosal bone tissue and in the areas of the load application. The largest loads were normal tension and compressive stresses in the plate due to its curve with maximum performance at the edge the hole for the third top screw from the internal part of the plate. The value of expansion of the fracture was not significant. Conclusions: The proposed fixateur has shown its high efficiency. It is important to consider the characteristics associated with the nature of the maximum stresses arising in areas of concentration, and not to produce constructs for osteosynthesis of brittle materials.